Students’ Perceptions of The Use Of ‘TELL’ in English Learning Process in Bosowa University Makassar - Indah Yuliana Muhtar; Abidin Pammu; Nasmilah Nasmilah (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
Technology in language teaching has become an incredibly important part of current pedagogy. The present study seeks to justify the perceptions of students about the use of Technology Enhanced Language Learning (TELL)  in the process of learning English in Bosowa University Makassar. A quantitative research design was employed as the approach to gathering data about the perception of the students. The questionnaire was used to cater as the research tools for the achievement of research goals. Descriptive statistic was performed to analyze the obtained data through questionnaires. The findings confirm that students have gained benefit in terms of language learning with the use of technologies.